2019
DOI: 10.1155/2019/8191689
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulphate and Chloride Ingress on Selected Cements Mortar Prisms Immersed in Seawater and Leather Industry Effluent

Abstract: Cement structures are major capital investments globally. However, exposure of cement-based materials to aggressive media such as chloride- and sulphate-laden environments such as coastal areas affects their performance. Ordinary Portland cement (OPC) is the main cement used in buildings and civil structures such as dams and bridges. This paper reports the findings of an experimental investigation on the effect of ingress of Cl− and SO42− on compressive strength development and the ions’ diffusivity in selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Both the SiO 2 and the Al 2 O 3 (Table 2), are very important for the reaction of the mordenite-clinoptilolite with the Ca(OH) 2 in solution; in this sense, Rosell-Lam et al [11] reached a similar conclusion. This favours the fixation of free lime and the neutralisation of calcium hydroxide in solution, avoiding the later reaction with sulphates and chlorides [32]. The pozzolanic reactivity influences favourably the mechanical strength of the cement, mortars and concrete [33].…”
Section: Results Of the Eight-day Pozzolanicity Analysis To Determine The Pozzolanic Reactivity Of The Samplesmentioning
confidence: 99%
“…Both the SiO 2 and the Al 2 O 3 (Table 2), are very important for the reaction of the mordenite-clinoptilolite with the Ca(OH) 2 in solution; in this sense, Rosell-Lam et al [11] reached a similar conclusion. This favours the fixation of free lime and the neutralisation of calcium hydroxide in solution, avoiding the later reaction with sulphates and chlorides [32]. The pozzolanic reactivity influences favourably the mechanical strength of the cement, mortars and concrete [33].…”
Section: Results Of the Eight-day Pozzolanicity Analysis To Determine The Pozzolanic Reactivity Of The Samplesmentioning
confidence: 99%
“…With rapid development of construction technology, concrete structure was inevitably exposed to various harsh environments, mainly including chloride attack, freezingthawing, and carbonation environments [1][2][3]. In particular, chloride penetration frequently resulted in the steel corrosion of reinforced concrete and reduced its service life, which was a key indicator for concrete durability [4,5]. Worldwide scholars have conducted a mass of studies to investigate the chloride penetration into concrete, and they found that the chloride penetration was different when concrete subjected to various exposure environments; moreover, the capillary absorption, concentration gradient, and convection provided the main driving force for chloride penetration into concrete [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…e durability of cement-based structures is a global pervasive problem. In view of changing environmental conditions due to climate change, there is a need to evaluate the performance of blended cements in aggressive media such as carbonation-prone environments [31,32]. e carbonationinduced corrosion is the major cause of degradation and subsequent reduction in the service life of cement-based materials and increased maintenance-related costs more so in structures located in coastal and offshore regions [33,34].…”
Section: Introductionmentioning
confidence: 99%